Review on new approach methods to gain insight into the feto-maternal interface physiology - Menon, Ramkumar; Muglia, Louis J.; Levin, Lisa Hara (Frontiers in Medicine, 2023)
Non-human animals represent a large and important feature in the history of biomedical research. The validity of their use, in terms of reproducible outcomes and translational confidence to the human situation, as well as ethical concerns surrounding that use, have been and remain controversial topics. Over the last ten years, the communities developing microphysiological systems (MPS) have produced New Approach Method (NAMs) such as organoids and organs-on-a-chip. These alternative methodologies have shown indications of greater reliability and translatability than animal use in some areas, represent more humane substitutions for animals in these settings, and -with continued scientific effort -may change the conduct of basic research, clinical studies, safety testing, and drug development. Here, we present an introduction to these more human-relevant methodologies and suggest how a suite of pregnancy associated feto-maternal interface system-oriented NAMs may be integrated as reliable partial -/full animal replacements for investigators, significantly aid animal -/environmental welfare, and improve healthcare outcomes.